Motivasi Peran Serta Masyarakat dan Penerapan Sistem Pemantauan Lingkungan Berkala Terpadu dalam Pengendalian Pencemaran Sungai akibat Industri dan Pemukiman - Setiani, Onny; T, Noverita Dian; Hanani, Yusniar; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2002)
The aim of this research is to motivate community to participate on continuous monitoring  of the environment. The implementation of continuous environmental monitoring by community is expected to augment the achievement of  river pollution control program. The research  areas were located on Plumbon and Beringin river basin on Semarang City as representative of industrial area, Kreo and Garang River basin as representative of settlement area. The research was conducted in 2 stages. The first stage was to examine water quality, environmental sanitation and community characteristics determination.  Situation analysis was performed for program planning based on collected data. The motivation  program was implemented in this stage.  The second stage was observational research to evaluate the community participation on environmental conservation. The achievement parameter is the improvement of community participation and river  water quality.  The research was conducted from July 1999 until June 2001. The results  show in all research areas before motivation  program implementation the community behavior was not support the environmental conservation. This condition was confirmed by poor sanitation and the rivers were heavily polluted. After program implementation, the community participation was improved, the people participation was shown by developing environmental conservation  cadre. The achievement was shown by the improvement of river water quality. In conclusion, community participation is able to improve the quality of environment, however, the government  support is necessary. Keywords: Community participation, continuous monitoring, river pollution, industry, settlement